Zintegrowany system wsparcia studentów we współczesnej edukacji – dobre praktyki - Kot-Radojewska , Magdalena (Studia Edukacyjne, 2018)
The paper argues about the role of higher education not only in terms of knowledge transfer andacquisition of vocational skills among young people, that is, the creation of qualified human capital for the needs of the economy, but also in terms of implementation of the educational role of the university, one currently underrated. It is aimed at the education of creative, open-minded, responsible graduates, capable of understanding a dynamically changing reality, able to adapt to changes flexibly, and accept responsibility for their own development. The article presents an example of good practices in the field of comprehensive student support in higher education as developed by the University of Dąbrowa Górnicza. This approach, in addition to improving the professional potential of students, is also focused on forming their values, goals, attitudes and beliefs which will significantly affect their behavior and the way they use the acquired knowledge in the future.